2014
DOI: 10.1073/pnas.1411649111
|View full text |Cite
|
Sign up to set email alerts
|

Proteopathic tau seeding predicts tauopathy in vivo

Abstract: Transcellular propagation of protein aggregates, or proteopathic seeds, may drive the progression of neurodegenerative diseases in a prion-like manner. In tauopathies such as Alzheimer's disease, this model predicts that tau seeds propagate pathology through the brain via cell-cell transfer in neural networks. The critical role of tau seeding activity is untested, however. It is unknown whether seeding anticipates and correlates with subsequent development of pathology as predicted for a causal agent. One majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
833
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 539 publications
(865 citation statements)
references
References 63 publications
29
833
3
Order By: Relevance
“…Seeding properties of many FTDP-17 mutants had yet to be examined, and current cultured cell tau seeding models tend to utilize either mutated truncated repeat domain (RD) tau (29,44,47), which can intrinsically aggregate in these models (56, 57), or full-length tau mutants at the P301 site (30). WT tau has been reported to aggregate with seeding in some cell culture studies, albeit only at low levels, especially when compared to P301L tau or RD tau (29,30,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeding properties of many FTDP-17 mutants had yet to be examined, and current cultured cell tau seeding models tend to utilize either mutated truncated repeat domain (RD) tau (29,44,47), which can intrinsically aggregate in these models (56, 57), or full-length tau mutants at the P301 site (30). WT tau has been reported to aggregate with seeding in some cell culture studies, albeit only at low levels, especially when compared to P301L tau or RD tau (29,30,48).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, there is a lack of data in the field comparing the seeding propensities of multiple tau mutants and much of the current data utilizes specific mutants P301L and P301S, or truncated repeat domain (RD) tau (29,30,(44)(45)(46)(47). However, disease phenotypes in FTDP-17 vary significantly between mutants and even within the same family (13).…”
Section: Introductionmentioning
confidence: 99%
“…We found that tauHMW was able to initiate tau aggregation in HEK TauRDP301S‐CFP/YFP cells (Holmes et al , 2014; Fig 5D), and, excitingly, showed rapid (1–2 min) phase separation into droplets as well as aggregation when applying crowding conditions (10% PEG, Fig 5E). Furthermore, by immunohistological labeling of phospho‐tau in post‐mortem human brain tissue with mild AD pathology (Braak stage III; Braak & Braak, 1995), we could find spherical phospho‐tau accumulations in hippocampal neurons (Fig EV6).…”
Section: Resultsmentioning
confidence: 79%
“…HEK293 cells stably expressing the repeat domain (TauRD, aa243‐372) of human mutant Tau441P301S tagged with CFP and YFP (HEK TauRDP301S‐CFP/YFP (Holmes et al , 2014)] were treated with preformed p‐tau441 droplets, soluble p‐tau441 [0.5 μM tau, 0.8% lipofectamine (LifeTechnologies)], or TauHMW from human AD brain lysates (20 ng tau, 0.8% lipofectamine). Treating these cells with tau material competent of seeding tau aggregation results in intracellular aggregation of TauRDP301S‐CFP/YF, which can be detected as small fluorescent FRET‐positive protein aggregates.…”
Section: Methodsmentioning
confidence: 99%
“…Animal (Clavaguera et al, 2009;Frost et al, 2009;de Calignon et al, 2012;Kfoury et al, 2012) and cell culture studies suggest that tau aggregation can propagate from neuron to neu-ron (Frost et al, 2009, Holmes et al, 2014 and there is growing interest in how tau is released and taken up by cells.…”
Section: Introductionmentioning
confidence: 99%